2005
DOI: 10.1111/j.1439-0396.2005.00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Beet‐vinasse (condensed molasses solubles) as an ingredient in diets for cattle and pigs – nutritive value and limitations

Abstract: Sugar beet vinasse, originating as the condensed molasses residue from yeast production, was fed to bulls and pigs to determine the feed value. It contained, per kg dry matter (DM content 66.8%), 293 g crude protein, 305 g N-free extract (therefrom 34.4 g total sugar), and 395 g crude ash. The experiment was carried out with three fattening bulls (German Holstein) and four adult pigs (Gottingen Minipig). In bulls, two balance trials lasting 20 days each (10 days adaptation; 10 days collection) were conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 8 publications
1
27
0
1
Order By: Relevance
“…In this study, there was no significant difference in fecal noxious gas emission among the treatments. There are no reports on the effect of molasses on fecal noxious gas emission, and there are only some studies assessing the effect of molasses on the DM in feces (Velázquez et al, 1969;Perez et al, 1983;Stemme et al, 2005). Therefore, it is difficult to explain the results of this study, and more studies on this aspect are needed.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In this study, there was no significant difference in fecal noxious gas emission among the treatments. There are no reports on the effect of molasses on fecal noxious gas emission, and there are only some studies assessing the effect of molasses on the DM in feces (Velázquez et al, 1969;Perez et al, 1983;Stemme et al, 2005). Therefore, it is difficult to explain the results of this study, and more studies on this aspect are needed.…”
Section: Discussionmentioning
confidence: 83%
“…One of the trials in growing swine performed by Brooks (1967) demonstrated that DM digestibility was not influenced by 20% molasses treatment compared with the basal group (without molasses). However, digestibility was decreased with the highest level of condensed molasses solubles (of DM by 43%) in finishing pigs (Stemme et al, 2005). Compared with starch treatment, digestibilities of DM and energy were significantly reduced in the treatment containing 68.5% molasses in growing pigs .…”
Section: Discussionmentioning
confidence: 91%
“…The main organic acids present in the vinasses are oxalate, lactate, acetate and malate, together with pyruvate. It is high in potassium and sulphates content (Troccon & Demarquilly 1989;Stemme et al 2005), so vinasse can be used for animal feed ingredient as a source of nutrients and minerals (Stemme et al 2005;LopezCampos et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In response to Searchinger's analysis, Croezen & Brouwer (2008) suggested that wheat (W‐) DDGS produced in Europe would substitute locally produced wheat and maize, but also soya bean meal (SBM) originating in South America. Other protein‐rich coproducts include vinasse (up to 35 g 100 g −1 ; Stemme et al , 2005) originating from spent yeast cells and unfermented sugars during production of bioethanol from beet sugar. This fraction is often added back to the sugar beet pulp (SBP) to give a feed which has a crude protein content in the range 10.6–13.5 g 100 g −1 (Ministry of Agriculture Fisheries & Food, 1975).…”
Section: Introductionmentioning
confidence: 99%